2016
DOI: 10.1080/21565503.2016.1164065
|View full text |Cite
|
Sign up to set email alerts
|

Race, partisanship, and perceptions of inter-minority commonality

Abstract: Feelings of commonality are central to the formation of multiracial political coalitions. Despite a fairly voluminous literature on where these feelings come from, however, relatively little is known about how elite messages influence individual-level perceptions of intergroup relations. This oversight is surprising given that socalled "elite opinion" theory has become "virtually orthodoxy" within political science. In order to explore the potential for opinion leadership on perceptions of commonality, this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In this article, we examine factors associated with perceptions of political commonality with African Americans among AAAUS. On the basis of prior studies on perceptions of intergroup commonality between racial minorities (Glasford and Calcango 2012; Nteta and Wallsten 2017; Sanchez 2008; Wallsten and Nteta 2012, 2017; Wilkinson 2014), we test the influence of group consciousness, linked fate, and experiences of discrimination on perceived political commonality with African Americans among AAAUS. A large body of work has assessed perceptions of commonality between racial minorities.…”
mentioning
confidence: 99%
“…In this article, we examine factors associated with perceptions of political commonality with African Americans among AAAUS. On the basis of prior studies on perceptions of intergroup commonality between racial minorities (Glasford and Calcango 2012; Nteta and Wallsten 2017; Sanchez 2008; Wallsten and Nteta 2012, 2017; Wilkinson 2014), we test the influence of group consciousness, linked fate, and experiences of discrimination on perceived political commonality with African Americans among AAAUS. A large body of work has assessed perceptions of commonality between racial minorities.…”
mentioning
confidence: 99%
“…We might have expected the policy-centric emphasis of our treatment to mitigate the impact of clergy messages on feelings of sympathy for the undocumented. We might have also expected limited leadership effects on the question of sympathy in light of an extensive body of research showing that elite rhetoric often fails to shape opinions about issues or groups that people have personal experience with (Zaller 1992; Karp 1998; Paul and Brown 2001; Wallsten and Nteta 2016). Indeed, given that a sizeable number of Americans report having direct contact with undocumented immigrants (Marrow 2011), the probability of finding significant differences between our treatment and control groups should have been very small.…”
Section: Discussionmentioning
confidence: 99%
“…While studies testing the social context approach consistently found that the size of out-groups is a significant predictor of perceptions of threat and competition among members of different groups, other studies report that racial contact lessens racial antagonism (Ellison and Powers 1994; Sigelman and Welch 1993; Welch et al 2001). Some of these studies find that intergroup contact can even lead to cooperation and support among groups under the right conditions (Allport 1954; Gaertner et al 1994; Glasford and Calcgno 2012; Kinder and Mendleberg 1995; Pettigrew 1998; Sigelman et al 1996; Wallsten and Nteta 2017; Wilkinson 2014; Wilkinson and Earle 2013; Wilkinson, Garand, and Dunaway 2015).…”
Section: Intergroup Contact and Racial Attitudesmentioning
confidence: 99%